(untitled) (Academia Science Repository, 2023)
Learning good English means getting all the significant moments of a native’s speech and correct expression of yours in a foreign language. It is very important to be strongly motivated to study a foreign language at a professional level. Whenever we teach a foreign language there must be a perfect goal which gives the students an impetus and makes them move to achieve the goal. The attitude to mastering a foreign language determines the content and organization of the educational process.